Point-of-Care Testing of Immunosuppressants in Blood Using Thin-layer Paper Spray Ionization and a Miniature Mass Spectrometer - XIE Yi-qing1,2;GUO Xiang-yu1;ZHANG Wen-peng3;OUYANG Zheng3;MA Qiang1 (Zhipu Xuebao, 2023)
A new method was proposed for point-of-care testing (POCT) of immunosuppressants in blood using thin-layer paper spray ionization and a miniature mass spectrometer. The aluminum thin-layer plate was used as paper spray substrate, and cut into an equilateral triangle. Aliquots of 10 μL blood sample were loaded on the aluminum thin-layer plate, and then 20 μL methanol was dropped as elution/spray solvent. The tip of the triangular plate was placed 1.0 cm in front of the discontinuous atmospheric pressure interface (DAPI) of the miniature mass spectrometer. When the spray voltage was applied, the sample was eluted from the triangular plate and formed paper spray ionization at the tip. Coupled with the miniature mass spectrometer, five immunosuppressants were detected under negative ion mode. The precursor ions ［M-H］- of tacrolimus, sirolimus, everolimus, ciclosporin A, and mycophenolic acid are m/z 802.6, 912.6, 957.1, 1 200.8, 319.1, and product ions are m/z 560.2 and 604.3, m/z 590.3 and 321.2, m/z 590.3 and 365.2, m/z 1 088.8, m/z 287.4 and 275.1, respectively. Based on the observed signal-to-noise ratio (S/N) of the most intense tandem mass spectrometry (MS/MS) fragment peaks and using the S/N=3 and 10 as the criteria, the limits of detection (LODs) and quantitation (LOQs) are estimated to be 0.5-5 mg/L and 1-10 mg/L, respectively. The internal standard method was used for quantitative analysis, and indapamide was used as the internal standard compound. Sufficient linearity for each analyte is obtained with the correlation coefficients (r) greater than 0.99. The proposed method displays good recoveries in the range of 91.0%-114.3% with the relative standard deviations (RSDs) less than 8.4%. Moreover, the developed method was used for the analysis of blood samples, which spiked with tacrolimus, sirolimus, everolimus, cyclosporine A and mycophenolic acid at the concentration of 100 mg/L. The analytical results demonstrated the consistency between the proposed method and the traditional liquid chromatography-mass spectrometry (LC-MS) method. The entire analysis procedure can be completed within 1 min. The proposed method is simple, fast, accurate, efficient, and suitable for POCT of immunosuppressants in blood.